Progress of Trachoma Mapping in Mainland Tanzania: Results of Baseline Surveys from 2012 to 2014. (1st November 2016) - Mwingira, Upendo J.; Kabona, George; Kamugisha, Mathias; Kirumbi, Edward; Kilembe, Bernard; Simon, Alistidia; Nshala, Andreas; Damas, Deogratias; Nanai, Alphonsina; Malecela, Mwelecele; Chikawe, Maria; Mbise, Christina; et al.
ABSTRACT: Purpose : Following surveys in 2004–2006 in 50 high-risk districts of mainland Tanzania, trachoma was still suspected to be widespread elsewhere. We report on baseline surveys undertaken from 2012 to 2014. Methods : A total of 31 districts were surveyed. In 2012 and 2013, 12 at-risk districts were selected based on proximity to known trachoma endemic districts, while in 2014, trachoma rapid assessments were undertaken, and 19 of 55 districts prioritized for baseline surveys. A multi-stage cluster random sampling methodology was applied whereby 20 villages (clusters) and 36 households per cluster were surveyed. Eligible participants, children aged 1–9 years and people aged 15 years and older, were examined for trachoma using the World Health Organization simplified grading system. Results : A total of 23, 171 households were surveyed and 104, 959 participants (92.3% of those enumerated) examined for trachoma signs. A total of 44, 511 children aged 1–9 years and 65, 255 people aged 15 years and older were examined for trachomatous inflammation–follicular (TF) and trichiasis, respectively. Prevalence of TF varied by district, ranging from 0.0% (95% confidence interval, CI 0.0–0.1%) in Mbinga to 11.8% (95% CI 6.8–16.5%) in Chunya. Trichiasis prevalence was lowest in Urambo (0.03%, 95% CI 0.00–0.24%) and highest in Kibaha (1.08%, 95% CI 0.74–1.43%). Conclusion : Only three districts qualified for mass drug administration with azithromycin. Trichiasis is still a public health problem in many districts, thus community-based trichiasis surgery should be considered to prevent blindness due to trachoma. These findings will facilitate achievement of trachoma elimination objectives.